Sociocultural Based Traditional Games and Their Relevance to Islamic Education Practices: Study of The Introduction to Local Wisdom at Sakola Motekar Ciamis - Sri Wulan; Derry Ridwan Maoshul; Mohamad Erihadiana; Tatang Muh Nasir; Zohaib Hassan Sain (Institut Agama Islam An-Nawawi Purworejo, 2025)
This research examines the role of sociocultural-based traditional games as a medium for introducing local wisdom and strengthening Islamic values ​​in Sakola Motekar, Ciamis. A sociocultural approach is used to connect teaching with the socio-cultural context of students, and traditional games become an effective medium for internalizing Sundanese and Islamic cultural values. At this school, traditional games are used to teach togetherness, honesty, responsibility and local wisdom, thereby strengthening students' cultural identity and moral and spiritual character according to Islamic teachings. The research aims to answer four main questions: (1) How are traditional games integrated into educational practice? (2) What is the relevance of local values ​​in traditional games to Islamic teachings? (3) How do games support the teaching of Islamic values? (4) How can traditional game-based learning methods strengthen students' understanding of local wisdom and Islamic values? The research uses a qualitative approach with case studies through observation, interviews and documentation. The results show that traditional games containing sociocultural values ​​not only function as entertainment, but also as an effective educational medium that combines social, cultural, moral and spiritual values ​​that are in line with Islamic education.